An exploration of live experiences of Balik-Islam using interpretative phenomenological analysis. - Clamucha, Tiffany Gail C. (2017.)
The primary goal of this study was to explore and gain an understanding of how Balik-Islam made sense of their worlds as converts to Islam. With Interpretative Phenomenological Analysis (IPA) as a theoretical and methodological framework, I gathered data by conducting semi-structured interviews among six converts to Islam. The data gathered were analyzed with the use of the four-step analytical process of IPA. The analysis of accounts revealed two essential experiences in the everyday lives of Balik-Islam: their genuine involvement in Islam and their inner conflict and struggle against discrimination from both Muslim and non-Muslims. For the Balik-Islam, the essence of bein a convert is living the Qur?an life. The findings of my study point to the need to address the struggles of Balik-Islam as they deal with society?s stereotypes and moral exclusion. Results also prove useful in advocating dialogue between non-Muslim majority and the Muslim minority in order to promote openness, understanding, and solidarity between the two groups.
Thesis (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Islam; Balik-Islam.